Charging wireless sensor network security technology based on encryption algorithms and dynamic model - Yuanming Li; Wei Guo; Xuejun Meng; Wen Xia (International Journal of Distributed Sensor Networks)
With the popularization of the Internet, the related information technology is developing faster and faster, and the scale and complexity of the network are also increasing. Wireless networks cover all aspects of life, along with it, network security issues have gradually emerged. In recent years, network security vulnerabilities have been exposed continuously, from WiFi to Bluetooth, people gradually realize the security of wireless networks. The purpose of this article is to solve the existing security problems and study the operation process of RC4 and Advanced Encryption Standard algorithms, and the improvement scheme is put forward. This article is based on the inherent media access control address filtering technology of wireless network card; a dynamic security model for wireless networks is proposed and constructed. Devices accessing the network use 802.1x authentication method and distribute and set security status values for each device, the authentication server uses Remote Authentication Dial in User Service. This article uses the method of virtual private network encryption network to provide an encryption layer for communication between devices and wireless networks, thus, the data in network transmission can be encrypted and protected. In this article, the structure and strategy of Remote Authentication Dial in User Service are changed, in order to ensure the high security of wireless network equipment in the connection process. In the testing phase of this article, we have tested the model in detail several times. Tests are divided into middleman and session interception tests. A large number of test results show that this model can improve the security of wireless network and has good performance.